Phytochemical Characterization of Xerospermum Noronhianum - Tan, Pei Jean (2008)
Xerospermum noronhianum, locally known as gigi buntal (globe-fish’s teeth) or rambutan pachat (leech’s rambutan) is a species belonging to the Sapindaceae family. The Sapindaceae are generally well known as a prolific source of plant saponins. However, to date, there has been no systematic phytochemical and biological evaluation on this particular species. In the present study, several known compounds have been successfully isolated from various plant parts and solvent fractions of Xerospermum noronhianum. Three new triterpenoid saponins have been purified from the ethyl acetate and aqueous fractions of both stem and leaf of the plant. Through the use of high field NMR and mass spectroscopy, these saponins have been identified to be those of the oleanane-type, i.e 3-O-{α-L-rhamnopyranosyl(1→2)-β-D-fucopyranosyl}-28-O-{[α-Lrhamnopyranosyl( 1→2)][α-L-rhamnopyranosyl(1→6)]}-β-D-glucopyranosyl oleanolic acid, 3-O-{α-L-rhamnopyranosyl(1→3)-β-D-fucopyranosyl}-28-O-{α-Lrhamnopyranosyl( 1→4)}-β-D-glucopyranosyl oleanolic acid and 3-O-{α-Lrhamnopyranosyl( 1→2)-[3’,4’-diacetoxy-β-D-fucopyranosyl]}-28-O-{α-L rhamnopyranosyl(1→2)}-β-D-glucopyranosyl oleanolic acid. Several known compounds have also been isolated and identified as the free triterpenes namely lupeol, oleanolic acid, friedelin, 3β-hydroxy-29-nor-20-lupenone, 3β-hydroxy-lup-20(29)en-30-al, mixture of 3β-hydroxyolean-12-en-11-one and 3β-hydroxyurs-12-en-11-one; the flavonoid glycosides kampferol-3-O-rhamnoside, quercetin-3-O-rhamnoside; the benzoic acid derivatives 3,5-dihydroxy-4-methoxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid; as well as scopoletin, lupeol palmitate, and palmitic acid, mixture of β-sitosterol and stigmasterol and mixture of their glycosides. Oxidation of the major compound, lupeol, successfully yielded lupenone as the product. The crude extracts and isolated pure compounds were also further evaluated for their anti-cholinesterase activity, against two enzymes; acetylcholinesterase and butyrylcholinesterase, using thin layer chromatography bioautographic method. The inhibition activities of the test samples were expressed as pMIQ values, which represents the negative logarithm of the minimal inhibitory quantity (in moles) that produced the spot with the least observable whiteness. Generally, the crude extracts of stem, leaf and bark parts, all showed inhibition in the preliminary screening by giving white observable inhibition spots against a yellow-coloured background. The enzyme inhibiting constituents were, in part, found to be due to the triterpenoidal saponins, the free triterpenes as well as the sterol and its glycosides. However, the tested compounds were considered to be weakly active due to their low pMIQ values. Compounds with pMIQ values ≥ 10.5 is considered to be bioactive. All of the tested compounds in this study gave pMIQ value in the range of 1.7 to 3.7.